Confirmation of State-Owned Enterprise Finances as State Finance to Strengthen Attestation of Criminal Acts of Corruption in State-Owned Enterprises (SOEs) - Prabowo Setyo Aji; Hartiwiningsih Hartiwiningsih (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2024)
The researcher looks at the presence of state funds under the supervision of State-Owned Enterprises, which clearly still generates different interpretations of the matter of state financial situation. The researcher became interested in doing a legal study to assist in attesting elements of state financial losses in criminal activities of corruption inside State-Owned Enterprises. This paper aims to investigate and comprehend the presence of state finances in State-Owned Enterprises to support the attestation of aspects of state financial losses in State-Owned Enterprises in addressing criminal actions of corruption. Analyzing the legislative and case approaches helps one to adopt a normative juridical writing style. Since State-Owned Enterprises officials with strategic duties and authority and a significant part in the running of the national economy commit corruption offenses, they constitute a type of corruption as an unusual crime. Under the application of the unique nature of Lex Specialis of the Corruption Eradication Law, which follows the flow of state finances wherever the money is located, efforts aiming at strengthening attestation of state financial losses under the management of State-Owned Enterprises declare losses resulting from unlawful acts or fraud as state losses.